Potential of a combination of Heliconia psittacorum and its associated bacteria for phytoremediation. Issue 1 (August 2021) - Baharuddin, M I; Aweng, E R; Kutty, S R M; Mohd Roslan, S N; Hanaphi, R M
Abstract: Remediation has recently received a lot of attention to combat or deal with contaminated soil, water, or air. There are a few types of remediation technologies, such as microbiological remediation and phytoremediation, in which microbial remediation uses microorganisms as the agent, while phytoremediation uses flowers as the agent. H.psittacorum is a flower with phytoremediation and ecologically favorable potential. The study is aimed at learning more about the microorganisms that could help improve soil and water quality. Microbiological remediation uses microorganisms as the agent, while phytoremediation uses flowers as the agent to overcome contamination problems. H.psitacorum was found to be able to remove copper, zinc, and phosphorus from soil and groundwater. As a result, H.psittacorum's phytoremediation capacity was measured in soil and root samples. Microorganism awareness within the root pattern increased to 4.4 × 10 9 cfu/ml, whereas the soil pattern increased to 1.5 × 10 9 cm/ml. The concentration and identity of bacteria in roots and soil revealed information about these bacteria's ability to remove pollutants, while the water quality assessment demonstrated H.psitacorum's potential. These seven bacteria have been identified as having a historical mechanism that has proven to be effective in removing, transferring, and stabilizing pollutants. In addition, a water quality assessment demonstrated H.psitacorum's phytoremediation potential reduced copper, zinc, and phosphate concentrations in the water from 0.64 to 0.068 mg/l, and 0.513mg/l to 0. The concentration and identity of bacteria in roots and soil revealed information about these bacteria's ability to remove pollutants.